Therapy Okupasi dan Kognitif Lansia - I Wayan Suardana (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2016)
This study aims to determine the relationship of occupational therapy with cognitive status in the elderly. This study was designed as retrospective study a comparative studied that conducted on a sample of 60 people are selected for each by simple random sampling. From the analysis found there was relationship between occupational therapy with cognitive state of elderly with Chi-Square scores was 34.2 and p = 0.00 (P 0.05) and OR of 55 at α 0.05 CI: (11141-271509). Which means that elderly people who do not to do occupational therapy 55 times more likely to experience cognitive decline compared to the elderly given occupational therapy.